Didactic guides, a necessary resource for autonomous learning in Medical Education - Zulema Tamara Mesa Montero; Marlen Llanes Torres; Daimy Nualla Bolufé (Medisur)
The use of the didactic guides by the teacher was not frequent despite being a traditional resource in the teaching-learning process. It was not until after the scourge of COVID-19 that it reached a greater peak in the development of autonomous learning in students, especially linked to distance education. This article reflects on the importance of an adequate orientation of independent work by the teacher, who must provide the student with the resources to appropriate the necessary knowledge of the subject. However, in face-to-face education, advocating for the autonomy of learning requires teachers to develop guides that allow them not only to direct, but also to contribute to the organization of the student's work and their own.